Composition Analysis and Pharmacological Activity of Avocado/Soybean Unsaponifiable Products Used in the Treatment of Osteoarthritis - Lambert, Cécile; Bellemère, Gaëlle; Boyer, Gaëtan; Ponelle, Frank; Bauer, Thierry; Legeny, Marie-Christine; Baudouin, Caroline; Henrotin, Yves (Frontiers in Pharmacology, 2022)
Objective: Avocado/soybean unsaponifiables (ASU) are commonly used to treat OA symptoms. However, there are many ASU mixtures on the market with differing compositions and pharmacological activities. This study aimed to compare the composition and pharmacological activity of seven commercially available ASU products on human osteoarthritis chondrocytes. Methods: The contents of the lipidic part of ASU were characterized by gas chromatography analysis using a VARIAN 3400 chromatograph. The pharmacological activity of the ASU products was tested on human osteoarthritis chondrocytes cultured in alginate beads. Their effects were evaluated on aggrecan, interleukin (IL)-6 and -8 and matrix metalloproteases (MMP)-3 using immunoassays as well as on nitric oxide through measurement of nitrite via spectrometry. Results: PIASCLEDINE-ExpASU® showed a specific profile with the presence of chromatographic peaks corresponding to an alkyl furan fraction as well as alkyl triols. PIASCLEDINE-ExpASU®, Persemax, Insaponifiable 300, Arthrocen and Arthocare contained quantifiable amounts of tocopherol, while tocopherol was undetectable in Avovida and Saponic. Squalene was found only in PIASCLEDINE-ExpASU®. The abundance of sterols varied depending on the product. PIASCLEDINE-ExpASU® was the most active of the tested ASU products in inhibiting nitric oxide, IL-6 and IL-8 production by chondrocytes. With the exception of Saponic and Persemax, all the ASU mixtures either slightly or significantly increased aggrecan production. MMP-3 levels were significantly decreased by Insaponifiable 300 and PIASCLEDINE-ExpASU® and significantly increased by Saponic. Conclusion: The composition of PIASCLEDINE-ExpASU® is different to that of the other evaluated ASU mixtures. This specific composition explains its better pharmacological activity, including the higher inhibitory effect on pro-inflammatory and pro-catabolic factors. Our findings are helpful in providing a basis for understanding the symptomatic effect of PIASCLEDINE-ExpASU® in patients with osteoarthritis.